Pathways to urban sustainability : research and development on urban systems : summary of a workshop - Schaffer, Daniel, 1950-; Vollmer, Derek (National Academies Press, 2010)
"More than half of the world's people now live in cities. In the United States, the figure is 80 percent. It is worthwhile to consider how this trend of increased urbanization, if inevitable, could be made more sustainable. One fundamental shortcoming of urban research and programs is that they sometimes fail to recognize urban areas as systems. Current institutions and actors are not accustomed to exploring human-environment interactions, particularly at an urban-scale. The fact is that these issues involve complex interactions, many of which are not yet fully understood. Thus a key challenge for the 21st century is this: How can we develop sustainable urban systems that provide healthy, safe and affordable environments for the growing number of Americans living in cities and their surrounding metropolitan areas? To address this question, the National Research Council organized a workshop exploring the landscape of urban sustainability research programs in the United States. The workshop, summarized in this volume, was designed to allow participants to share information about the activities and planning efforts of federal agencies, along with related initiatives by universities, the private sector, nongovernmental groups, state and local agencies, and international organizations. Participants were encouraged to explore how urban sustainability can move beyond analyses devoted to single disciplines and sectors to systems-level thinking and effective interagency cooperation. To do this, participants examined areas of potential coordination among different R&D programs, with special consideration given to how the efforts of federal agencies can best complement and leverage the efforts of other key stakeholders. Pathways to Urban Sustainability offers a broad contextual summary of workshop presentations and discussions for distribution to federal agencies, regional organizations, academic institutions, think tanks and other groups engaged in urban research."--Publisher's website.